Association of interleukin-4, interleukin-13 gene polymorphisms, HLA-DQ and DR genotypes with genetic susceptibility of type-1 Diabetes Mellitus in Kuwaiti children - Mohammad Z. Haider; Maysoun Al Rushood; Maysoun Al Rushood; Hind Alsharhan; Hind Alsharhan; Majedah A. Rasoul; Maria Al-Mahdi; Hessa Al-Kandari; Hessa Al-Kandari (Frontiers Media S.A., 2023)
BackgroundType-1 diabetes mellitus (T1DM) is a complex multifactorial disease with an autoimmune etiology and is thought to result from an interaction between genetic and non-genetic factors. Cytokines play a crucial role in the pathogenesis of autoimmune diseases due to their effector and regulatory functions in immune responses. Interleukin-4 (IL4) and Interleukin-13 (IL13) are anti-inflammatory cytokines and are considered as important mediators in pathology of the autoimmune diseases.MethodsWe have determined the genotype frequency of IL4 gene promoter polymorphism (−590C/T, rs2243250), IL13 gene polymorphism p.(Arg130Glu, rs20541) and human leukocyte antigen, HLA-DQ and DR genotypes in Kuwaiti children with T1DM to investigate their role in genetic susceptibility. This study included 261 Kuwaiti children with T1DM and 214 healthy controls. The genotypes for IL4 (−590C/T) and IL13 p.(Arg130Glu) gene polymorphisms were detected by PCR-RFLP methods. HLA-DQ and DR genotypes were determined by sequence-specific PCR methods.ResultsThe CC genotype of IL4 gene polymorphism (−590C/T) was significantly related to the risk for T1DM in Kuwaiti patients (OR 1.64). The homozygous AA (QQ) and heterozygous AG (RQ) genotypes of IL13 gene polymorphism p.(Arg130Glu), also manifested a statistically significant association with T1DM (OR 2.92 and 4.79). In 55% T1DM patients, the HLA genotype was either DQ2/DQ2 or in combination with a DQ8 allele. Collectively, 91% Kuwaiti T1DM patients had either DQ2 or DQ8 alleles in different combinations highlighting them as the high risk-genotypes in comparison to the controls. In the case of HLA-DR, the genotypes DR3/DRB5, DR3/DR4, DR3/DR7 and DR4/DR4 showed highest frequency amongst the Kuwaiti T1DM patients and thus can be considered as high-risk genotypes when compared to the controls. A high degree of co-inheritance (>80%) was detected between IL4 and IL13 gene polymorphism genotypes (CC and QQ) and the high-risk HLA-DQ and DR genotypes amongst the Kuwaiti T1DM patients.ConclusionsWe have identified the association of IL4 and IL13 gene polymorphisms with susceptibility to T1DM in Kuwaiti children and the co-inheritance of these polymorphisms with high-risk HLA genotypes. The findings may contribute to early identification of childhood diabetes.